6 - Male Undergraduate Students’ Knowledge of and Attitude Towards Emergency Contraceptives - Ellen Mabel Osei – Tutu, (African Sociological Review, 2019)
This study sought to explore the relationship between male students’ knowledge and attitude towards emergency contraceptives. Self – administered questionnaires were used in collecting data from 941 male respondents who were in their second, third or fourth year at the University of Ghana. These respondents were conveniently sampled from the four Colleges of the University of Ghana. Employing the theory of knowledge, attitude and practice, this paper investigates male knowledge and attitude towards emergency contraceptives. Although some students had favourable and others had unfavourable attitude towards emergency contraceptives, most of them (82%) had mixed attitude towards emergency contraceptives. Multinomial logistic regression results showed that students who belonged to the College of Education were significantly more likely to have favourable than unfavourable attitude towards emergency contraceptives. Since men play active roles in decision – making processes in reproductive health matters it is important that they are involved in all reproductive health programmes. This, in the long run, will help reduce unintended and unplanned pregnancies and subsequently unsafe induced abortions.